Analysis of WRKY Resistance Gene Family in Boehmeria nivea (L.) Gaudich: Crosstalk Mechanisms of Secondary Cell Wall Thickening and Cadmium Stress - Feng, Xinkang; Abubakar, Aminu Shehu; Yu, Chunming; Zhu, Aiguo; Chen, Jikang; Chen, Kunmei; Gao, Gang; Wang, Xiaofei; Mou, Pan; Shao, Deyi; Chen, Ping (Frontiers in Plant Science, 2022)
A total of 60 WRKY family genes unevenly distributed across 14 chromosomes of ramie were identified. Most of the genes (72%) concentrated in the distal telomeric region. These genes were divided into seven distinct subfamilies groups: I, II (a, b, c, d, e) and group III. Group IIc contains only the variant of heptapetide sequence (WRKYGKK). Segmental duplication events (41.7%) were the main driver of BnGWRKY evolution. A total of 38 ramie genes have collinear relationships with 27 A. thaliana genes, 32 C. sativa, 5 O. sativa and 4 Z. mays genes. The number and density of cis-acting elements in response to stress and hormones were most prominent, with abundant ARE and rare LTR cis-acting elements show the long-standing adaptability of ramie to its natural environment. GO and KEGG enrichment analysis of the WRKY target genes revealed their involvement in response to stimuli, immune system processes, transporter protein activity and antioxidant activity. Twelve WRKY were selected and tested against Cd2+ stress response and the result showed all the 12 were activated by Cd2+ stress, and the degree of activation varied from site to site. Combining transcriptome, orthologous gene relationships and qPCR, we proposed a potential crosstalk mechanisms between secondary cell wall thickening and Cd2+ stress. BnGWRKY50 and BnGWRKY58, which were both directly or indirectly regulate lignin synthesis during secondary cell wall thickening are involved in GSH1-, DCD-, and PDR8-mediated Cd2+ stress regulatory systems. This thus, provided information into the role of BnGWRKY proteins in ramie secondary wall development and response to cadmium stress, and could serve as basis for ramie crop improvement.